A versatile MOF-based trap for heavy metal ion capture and dispersion - Peng, Yaguang; Huang, Hongliang; Zhang, Yuxi; Kang, Chufan; Chen, Shuangming; Song, Li; Liu, Dahuan; Zhong, Chongli (Nature communications, 2018)
Current technologies for removing heavy metal ions are typically metal ion specific. Herein we report the development of a broad-spectrum heavy metal ion trap by incorporation of ethylenediaminetetraacetic acid into a robust metal-organic framework. The capture experiments for a total of 22 heavy metal ions, covering hard, soft, and borderline Lewis metal ions, show that the trap is very effective, with removal efficiencies of >99% for single-component adsorption, multi-component adsorption, or in breakthrough processes. The material can also serve as a host for metal ion loading with arbitrary selections of metal ion amounts/types with a controllable uptake ratio to prepare well-dispersed single or multiple metal catalysts. This is supported by the excellent performance of the prepared Pd 2+ -loaded composite toward the Suzuki coupling reaction. This work proposes a versatile heavy metal ion trap that may find applications in the fields of separation and catalysis. Heavy metal removal from polluted water is of global significance, but current adsorbents are limited by their specificity towards certain metals. Here the authors incorporate a non-specific and strong chelating group into a robust metal-organic framework and demonstrate its versatility for heavy metal adsorption.